Evaluasi Dan Pengembangan Bisnis Usaha Sempol Ayam Mudzky - Muadz Abidzar Zaky; Ajeng Andriani Hapsari (ProBisnis : Jurnal Manajemen, 2025)
The Sempol Ayam business is a snack business that uses chicken as the main ingredient. Currently the Sempol Ayam Mudzky branch operates in the East Jakarta and South Jakarta areas. This business idea arose because of the COVID19 conditions, where the MSME business at that time was very influential on the wheels of the Indonesian economy. This business is online and offline based, using the gofood and grabfood platforms as online media and outlets as offline media. This study aims to determine the feasibility of the Sempol Ayam business in the Jakarta area in terms of market aspects, operational aspects, human resource aspects, financial aspects and strategic aspects. Researchers are targeting 2% of the total population in Jakarta. The study results show that the business is feasible to run from the aspects that have been tested.